Effects of a mixture of mulching film microplastics on soil properties, microbial activities, and plants in terrestrial mesocosms with and without earthworms - Šmídová, Klára; van Loon, Sam; Zantis, Laura J.; Adamczyk, Sylwia; de Jeu, Lotte; Hurley, Rachel; Kernchen, Sarmite; Consolaro, Chiara; Adamczyk, Bartosz; Nizzetto, Luca; Bosker, Thijs; Selonen, Salla; et al. (Elsevier, 2026)
The increasing use of plastics in agriculture, e.g., mulching films, may lead to an accumulation of microplastics (MPs) in soil. This study assessed the effects of a 1:1 mixture of MPs produced from two commonly applied types of mulching film, conventional low-density polyethylene (LDPE) based and biodegradable starch polybutylene adipate terephthalate (PBAT-BD) blend-based plastics, under realistic conditions in terrestrial mesocosms. To assess the potential role of earthworms on the effects of microplastics, the study included treatments with and without earthworms. After 12 weeks of exposure, effects were determined on different endpoints: soil pH, soil compaction, carbon and nitrogen mineralization, and plant growth and biochemistry. MPs increased soil compaction, especially in the absence of earthworms, suggesting that earthworm activity can mitigate their physical impact on soil structure. MPs stimulated soil respiration at high concentrations, while simultaneously reducing nitrogen mineralization. This suggests these MPs acted both as a stimulant and a stressor for soil microbial communities. Although plant growth and chlorophyll content were unaffected by MP exposure, significant biochemical responses in lettuce, such as oxidative stress and activation of defence mechanisms, indicate that MPs can impact plant health at the molecular level, even in the absence of visible symptoms. Nitrogen mineralization was significantly increased in the mesocosms with earthworms, probably due to bioturbation and consequent increased aeration of the soil. However, the presence of earthworms did not have significant effects on other microbial and plant-related endpoints, suggesting that the earthworms affected the toxicity of the MPs only to a limited extent.
Keywords: agricultural plastics; conventional and biodegradable plastics; soil respiration; plant growth; oxidative stress